2018
DOI: 10.3136/fstr.24.45
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of The Amount of Chickpea Sourdough and Dry Yeast in Wheat Bread Formulation: Evaluation of Physicochemical, Sensory and Antioxidant Properties

Abstract: The aim of this study was to optimize amounts of chickpea sourdough (A) and instant active dry yeast (B) in bread formulation and to evaluate the potential use of chickpea sourdough in bread production by examining various quality parameters.An experimental design suggested by Response Surface Methodology was used.The bread produced according to the optimized model (OBrd) was compared with control bread (CBrd) in terms of several quality parameters. According to the optimization results, optimum levels of usag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…All forms of CY significantly ( P < 0.05) increased the phenolic contents and antioxidant capacities of the breads in proportion to addition levels. Similar results were also obtained by other researchers 1,6,7 . Chickpea contains many different polyphenolic bioactive compounds, 37 and the quantity, solubility and composition of those substances are modified during fermentation 38,39 .…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…All forms of CY significantly ( P < 0.05) increased the phenolic contents and antioxidant capacities of the breads in proportion to addition levels. Similar results were also obtained by other researchers 1,6,7 . Chickpea contains many different polyphenolic bioactive compounds, 37 and the quantity, solubility and composition of those substances are modified during fermentation 38,39 .…”
Section: Resultssupporting
confidence: 88%
“…However, no significant volume effects were found on gluten‐free breads 7 . In another study, wet, conventionally dried (35 °C in an oven) and FD‐CY samples were used in breadmaking with almost no impact on loaf volume 5,6 . Xiao et al 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was discovered that the standard made with yeast, EW, and RF had significantly more browning than the other standard bread made only with EW and RF or the standard made with AC, EW, and RF. The reason might be attributed to the fact that yeast impacts bread color by producing secondary metabolites via several metabolic pathways via non-enzymatic chemical processes such as Maillard and caramelization [ 21 , 22 , 23 ], which generate brown colored chemicals during baking [ 24 , 25 , 26 ]. Moreover, it was found that the addition of 40% GH in the wheat bread along with gelling agents AC, EW, and RF further enhanced the physical appearance of the bread in comparison to the standards that were made alone with EW and RF or AC, EW, and RF combinations ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it was observed that the bread made with GH had less browning than the standard yeast bread. Yeast affects the color of the bread due to the production of secondary metabolites [ 33 , 34 ] through different metabolic pathways by non-enzymatic chemical reactions such as Maillard and caramelization, which produce brown colored compounds during the baking [ 35 , 36 , 37 ]. Table 1 shows the characteristics of the standard bread versus the GH bread.…”
Section: Resultsmentioning
confidence: 99%